1993
DOI: 10.1111/j.1432-1033.1993.tb17580.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical characterisation of a dehydroepiandrosterone sulfotransferase in rats and humans

Abstract: A member of the rat liver hydroxysteroid sulfotransferase (ST) enzyme family metabolising dehydroepiandrosterone (DHEA) was purified from female rats and used to raise rabbit polyclonal antibodies. Characterisation of this antibody preparation demonstrated that it was specific for DHEA ST, and recognised a single 30-kDa protein on immunoblot analysis of rat liver cytosol which was expressed preferentially in female rat liver, and immunohistochemical localisation of the protein in female rat liver determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…This may explain the liver specificity of the carcinogenic effect, as rHSTa is primarily a hepatic enzyme (16)(17)(18) and reactive sulfuric acid conjugates may not be readily transferred from one cell to another owing to their charge. For example, 1-hydroxymethylpyrene, a compound which is activated by SULTs, forms DNA adducts in SULT-proficient, parenchymal liver cells, but not in neighbouring, SULT-deficient, Kupffer cells in the rat (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain the liver specificity of the carcinogenic effect, as rHSTa is primarily a hepatic enzyme (16)(17)(18) and reactive sulfuric acid conjugates may not be readily transferred from one cell to another owing to their charge. For example, 1-hydroxymethylpyrene, a compound which is activated by SULTs, forms DNA adducts in SULT-proficient, parenchymal liver cells, but not in neighbouring, SULT-deficient, Kupffer cells in the rat (30).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, if α-hydroxytamoxifen is activated by SULT, then SULT2 enzymes are the most likely candidates. In the rat, hydroxysteroid sulfotransferase a (rHSTa) is the predominant SULT2 form; rHSTa is highly expressed in the liver, whereas in all other tissues that have been investigated its expression is very low or not detectable (16)(17)(18). In humans only a single SULT2 form, hHST is known (16).…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, the enzyme was not detected in human (11,12), mouse (13), or rat (12) brain, although some groups have found the enzyme in rat (14,15) and in frog (16) brain. Other studies have reported a very low hydroxysteroid sulfotransferase activity in rat (17) and human (18) brain.…”
mentioning
confidence: 98%
“…However, as DHEA-ST is distributed across the liver lobule [16], with perhaps higher activity found in periportal hepatocytes than perivenous [12], the activity in liver homogenate would be expected to be high as more cells express the enzyme in comparison to the kidney. The liver is the main site for endogenous and xenobiotic metabolism generally within the body, and the high activity of this phase II enzyme might also, therefore, be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Expression was only noted in liver and adrenals, with none being observed in kidney. The only previous report of DHEA-ST in rat kidney was made by Sharp et al [16]who postulated that it might represent a different isoform of sulphotransferase, since immunological studies showed a band of different molecular weight from the sulphotransferase isolated from the liver. In the rat kidney, DHEA also modulates expression of the cytochrome P-450 isoform [17].…”
Section: Introductionmentioning
confidence: 99%